Unipolar Latissimus Dorsi Transfer for Restoration of Elbow Flexion in Residual Post-traumatic Brachial Plexus Palsy Associated with Distal Humeral Fractures - Sadek, Ahmed Fathy; Ellabban, Mohamed A. (Journal of Hand and Microsurgery, 2021)
Introduction Elbow flexion is indispensable for both functioning and nonfunctioning hands. It is well perceived that restoration of elbow function is the first reconstructive priority in cases of brachial plexus injuries. The authors assessed the impact of associated distal humeral fractures on the functional outcome after unipolar latissimus dorsi transfer (ULDT) for restoration of elbow flexion in patients with residual brachial plexus palsy (BPP).Patients and Methods Twenty-three patients operated for restoring elbow flexion after residual post-traumatic BPP (with or without distal humeral fracture) by unipolar latissimus dorsi transfer (ULDT) were reviewed for a retrospective study. Patients were divided into two groups; associated distal humeral fracture group (HF-group; 10 patients) and non-associated distal humeral fracture group (NHF-group; 13 patients). Elbow flexion active range of motion (AROM), flexion deformity in addition to Mayo Elbow Performance Score (MEPS) were assessed.Results In both groups there were statistically better postoperative MEPS grading (p = 0.007, p = 0.001, respectively) and scoring with a mean of 81 ± 16.1 and 90 ± 4.6, respectively (p < 0.001). The mean postoperative elbow flexion AROM was statistically better in both groups. The mean supination AROM was better in NHF group (p = 0.057).Conclusion The use of ULDT in residual post-traumatic BPP is an efficient procedure in regaining functional flexion and supination. An associated distal humeral fracture does not significantly affect the final functional outcome.Level of Evidence Level IV.
Keywords: latissimus dorsi; restoration of elbow flexion; residual brachial plexus palsy; distal humeral fracture